Constraining non-thermal and thermal properties of Dark Matter - Dev, P. S. Bhupal; Mazumdar, Anupam; Qutub, Saleh (Frontiers in Physics, 2014)
We describe the evolution of Dark Matter (DM) abundance from the very onset of its creation from inflaton decay under the assumption of an instantaneous reheating. Based on the initial conditions such as the inflaton mass and its decay branching ratio to the DM species, the reheating temperature, and the mass and interaction rate of the DM with the thermal bath, the DM particles can either thermalize (fully/partially) with the primordial bath or remain non-thermal throughout their evolution history. In the thermal case, the final abundance is set by the standard freeze-out mechanism for large annihilation rates, irrespective of the initial conditions. For smaller annihilation rates, it can be set by the freeze-in mechanism which also does not depend on the initial abundance, provided it is small to begin with. For even smaller interaction rates, the DM decouples while being non-thermal, and the relic abundance will be essentially set by the initial conditions. We put model-independent constraints on the DM mass and annihilation rate from over-abundance by exactly solving the relevant Boltzmann equations, and identify the thermal freeze-out, freeze-in and non-thermal regions of the allowed parameter space. We highlight a generic fact that inflaton decay to DM inevitably leads to an overclosure of the Universe for a large range of DM parameter space, and thus poses a stringent constraint that must be taken into account while constructing models of DM. For the thermal DM region, we also show the complementary constraints from indirect DM search experiments, Big Bang Nucleosynthesis, Cosmic Microwave Background, Planck measurements, and theoretical limits due to the unitarity of S-matrix. For the non-thermal DM scenario, we show the allowed parameter space in terms of the inflaton and DM masses for a given reheating temperature, and compute the comoving free-streaming length to identify the hot, warm and cold DM regimes.